Models of Collapsing and Expanding Cylindrical Source in f(R,T) Theory - M. Sharif; Aisha Siddiqa (Advances in High Energy Physics)
We discuss the collapsing and expanding solutions of anisotropic charged cylinder in the context of f(R,T) theory (R represents the Ricci scalar and T denotes the trace of energy-momentum tensor). For this purpose, we take an auxiliary solution of Einstein-Maxwell field equations and evaluate expansion scalar whose negative values lead to collapse and positive values give expansion. For both cases, the behavior of density, pressure, anisotropic parameter, and mass is explored and the effects of charge as well as model parameter on these quantities are examined. The energy conditions are found to be satisfied for both solutions.